(3GdgOGjI aj ePgH GdEeGe CMeO Hf MfHds - (3eMahX Hf CMeO Hf GdMSf GdcdhPGfj, CHh GdNWGH,J (B510 (3g` s ((3GHh HcQ Hf ehSi GHf CHj HcQ GHf GdMGL YeQ GdMfHdi s)
(3ChdgG (B:s
(3bGd GdTjN GdcdhPGfi gPG eNJUQ PcQJ ajg LedkG ef GUhd ePgH Hf MfHd cJGH GdWgGQI bGd Gddg JYGdi hGfRdfG ef GdSeGA eGA WghQG s
(3BNQgG (B:s
(3aEf cGf ai CLRGA GdMHI cSQGJ HSWJ GdMHGJ ef LfS Pdc GdcSQ hHSWJ GdaVdg GdefShHI cPdc CjVkG Ke fSHJgG ef Pdc ceG HjfG BNQ GdcJGH s
(3HChdgG ChQGb HNW MOjK bhHd HYVg Ydi fSNI bOjeI HecJHI GdSdjeGfjI HJQcjGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B291 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B188s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs